Ampliação de distribuição geográfica de morfotipos de galhas e galhadores da família Cecidomyiidae (Diptera) em espécies do gênero Andira Lam. (Fabaceae) no Brasil - Silva, Eduardo Alves Martins (Universidade Federal de São Carlos, 2021)
Galls are structures formed by the modification of plant tissue by the action of agents such as viruses, bacteria, nematodes, and, mainly, insects. Most known galls are induced by dipterans of the Cecidomyiidae family. Many gall morphotypes can be found in host plants simultaneously. Their presence is a marker to identify the gall makers because there is a species-specific interaction between gall makers and host plant species. This study aimed to search for records of the occurrence of morphotypes induced by cecidomyiids in Andira Lam. species distributed in Brazil to expand the geographical distribution of gall morphotypes and, consequently, of their gall makers. The study was carried out through the search for records of gall morphotypes in Andira species in the database of scientific articles and in Brazilian and abroad virtual herbaria. As results were found records for six species of Andira, which are Andira cujabensis Benth, Andira fraxinifolia Benth., Andira humilis Mart. ex Benth., Andira nitida Mart. ex Benth., Andira surinamensis (Bondt) Splitg. ex Amshoff, and Andira vermifuga (Mart.) Benth. In addition to the distribution registered in the original description of the gall makers –which usually cover only the type-locality– two new records of occurrence were found for Andira fraxinifolia and Andira nitida each, four for Andira humilis and six for Andira vermifuga. With these new records of occurrence, there was an expansion of geographic distribution to six new locations in Brazilian states already sampled, and new occurrences to the states of Bahia, Paraíba, Goiás, Ceará and Distrito Federal.
Expansion of geographic distribution of morphotypes of galls and gall makers of the family Cecidomyiidae (Diptera) in species of the genus Andira Lam. (Fabaceae) in Brazil.
Keywords: Andira fraxinifolia; Andira humilis; Andira nitida; Andira vermifuga; Herbário Virtual; Interação espécie-específica; Virtual herbarium; Species-specific interaction; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES